PENYULUHAN KESEHATAN ASI EKSKLUSIF, TEKNIK MENYUSUI DAN PENANGANAN PUTING SUSU LECET DI JETIS - Nurul Agustin (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2021)
Abstract Health development is an effort to fulfill one of the people's rights, especially in the health sector. One way to improve health development is to develop human resources from an early age through exclusive breastfeeding.Breastfeeding is a scientific process. Millions of mothers around the world are able to breastfeed their babies without ever reading a book about breastfeeding, even illiterate mothers can breastfeed their children well. However, in our current cultural environment, doing things naturally is not always easy. When breastfeeding for the first time, breastfeeding mothers generally feel pain or tenderness in the nipples. This is normal, but if the pain or stinging is excessive and even accompanied by sore nipples, then this is not normal and requires treatment. Some researchers have found that sore or sore nipples are generally caused by breastfeeding and improper latch on.